(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article examines current trends in corporate taxation driven by globalization, digitalization, and geopolitical instability. New strategies for optimizing companies’ tax burdens, as well as the associated risks, are analyzed. Emphasis is placed on legal approaches to tax planning, the transformation of tax functions, and the importance of tax risk management in a rapidly changing world.